2009
DOI: 10.1021/jp901073s
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of Anthracene-9,10-endoperoxide

Abstract: The wavelength dependence of the photochemistry of anthracene-9,10-endoperoxide (APO) in acetonitrile was quantitatively investigated at 5 degrees C, with excitation varied from 240 to 450 nm. Anthracene (AC) and a diepoxide (DE) were identified as the main primary photoproducts. After short exposure times DE was at all wavelengths the dominating photoproduct, while AC was only formed for lambda Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 29 publications
0
70
0
Order By: Relevance
“…This result is in agreement with the recently calculated energy paths 13 and the available experiments that found that 1 O 2 is obtained after excitation to states higher than the S 1 . 9 The present quantum dynamic simulations cannot provide the pathways to form rearrangement products due to the limited consideration of DOFs. Such rearrangements of the molecule require much more complicated DOFs, which are impossible to be described by a simple model Hamilton operator.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This result is in agreement with the recently calculated energy paths 13 and the available experiments that found that 1 O 2 is obtained after excitation to states higher than the S 1 . 9 The present quantum dynamic simulations cannot provide the pathways to form rearrangement products due to the limited consideration of DOFs. Such rearrangements of the molecule require much more complicated DOFs, which are impossible to be described by a simple model Hamilton operator.…”
Section: Discussionmentioning
confidence: 96%
“…1) it has been established that the cycloreversion is preferred after excitation to higher lying singlet states S n (n ≥ 2), whereas excitation to the S 1 exclusively entails the O-O cleavage. 9 The S 1 of APO was found to correspond to a π * OO → σ * OO transition. 10,11 This assignment is in agreement with considerations of the orbitals contributing to a Diels-Alder type of reaction.…”
Section: Introductionmentioning
confidence: 99%
“…In contrary to the latter mentioned polymer matrix crosslinking reactions, depending on the reaction conditions, a vigorous degradation of polysaccharide hyaluronic acid by singlet oxygen liberated from POA was reported earlier [8]. The possibility of endoperoxides to release these reactive species by unimolecular decomposition makes them interesting candidates for in vivo site-specific oxidative targeting with singlet oxygen at the present time [6,9]. The complex oxygen photosensitization in the presence of water soluble anthracene-1-sulphonate was studied by means of EPR spin trapping method [10].…”
Section: Introductionmentioning
confidence: 87%
“…These thermally and photo chemically reactive substances (depending on the reaction conditions) are decomposed to the original hydrocarbon and simultaneously liberate singlet oxygen ( 1 O 2 ), or decompose by the disruption of the O-O bonds, thus producing highly reactive biradical, or finally by the transformation into the other types of peroxides [4]. For instance, for anthracene-9,10-endoperoxide (POA) it has been found, that its photochemical excitation to S n , with n ≥ 2 leads to cycloreversion, producing anthracene and 1 O 2 , whereas excitation to the S 1 state would initially cause homolytic O-O cleavage, eventually resulting in a diepoxide rearrangement product [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the superoxo radical (d) was rapidly reduced by the e -at the para position of the triazine ring on g-C 3 N 4 , producing the 1,4-endoperoxide species (f) [81]. Protonation of the endoperoxide species produced H 2 O 2 [80,82] and completed the photocatalytic cycle.…”
Section: Graphitic Carbon Nitride (G-c 3 N 4 ) Photocatalystmentioning
confidence: 99%